Clinical efficacy of low-level laser therapy in plantar fasciitis: A systematic review and meta-analysis. Issue 3 (January 2019) - Wang, Wei; Jiang, Weifeng; Tang, Chuanxi; Zhang, Xiao; Xiang, Jie
Abstract: Background: Emerging evidence suggests that low-level laser therapy (LLLT) for plantar fasciitis (PF) may be beneficial. However, the convincing study investigating its effectiveness for treatment of PF was scarce. Therefore, a systematic review and meta-analysis was conducted to assess whether LLLT significantly relieve pain of patients with PF. Methods: PubMed, EMBASE, EBSCO, Web of Science, China Biological Medicine Database, China National Knowledge Infrastructure, Chinese Wan fang, and Cochrane CENTRAL were searched systematically up to March 2018. Results: A total of 6 randomized controlled trials were included. The meta-analysis indicated that compared with control group, visual analogue scale (VAS) score significantly decreased at the end point of the treatment in LLLT group. In addition, this improvement is continued for up to 3 months. However, no significant difference was observed according to the Foot Function Index-pain subscale (FFI-p). Conclusion: This meta-analysis indicates that the LLLT in patients with PF significantly relieves the heel pain and the excellent efficacy lasts for 3 months after treatment.